CanFlyet: habitat zone and diet trait dataset for Diptera species of Canada and Greenland - Samantha Majoros; Tyler Elliott; Sarah Adamowicz (Biodiversity Data Journal)
Flies (Diptera) are an ecologically important group that play a role in agriculture, public health and ecosystem functioning. As researchers continue to investigate this order, it is beneficial to link the growing occurrence data to biological traits. However, large-scale ecological trait data are not readily available for fly species. While some databases and datasets include fly data, many ecologically relevant traits for taxa of interest are not included. In this study, we create a dataset containing ecological traits (habitat and diet) for fly species of Canada and Greenland having occurrence records on the Barcode of Life Data Systems (BOLD). We present a dataset containing trait information from the literature for 981 Diptera species.Diptera species were chosen for the dataset, based on the occurrence records available for Diptera species from Canada and Greenland on the Barcode of Life Data System (BOLD). Trait data were then compiled and digitised in a standardised format, based on 667 works from literature published before April 2024. Traits were assigned at the lowest taxonomic level available. Three biological traits were included: larval habitat, larval diet type and adult diet. The dataset contains traits for 981 species across 380 genera, 34 subfamilies and 61 families. This dataset allows for assignment of traits to occurrence data for Diptera species and can be used for further research into the ecology, evolution and conservation of this order.